"Pengataa” and “Nalodo” Natural Disasters with a Phenomenology Approach in Central Sulawesi Indonesia“Pengataa” and “Nalodo” Natural Disasters with a Phenomenology Approach in Central Sulawesi Indonesia - Siradjuddin, Zaenal (International Journal For Research In Social Science And Humanities, 2021)
As the largest archipelagic country, Indonesia can potentially have disasters such as volcanic disasters marked by volcanic rings and several earthquake faults that can cause potential earthquakes. Central Sulawesi has the Palu Koro earthquake fault, which periodically causes earthquakes. The Kaili tribe spread across Central Sulawesi has local wisdom about unified environmental management, particularly the "Nalodo" land movement disaster called "Pengataa," which contains guidelines for environmental management to minimize the impact on society from disasters such as "Nalodo." Research on "pengataa" is needed to restore public knowledge on how to minimize and impact disasters. This study aims to reveal the phenomenon of "Pengataa" in the ToKaili community facing disasters. This study uses a qualitative method with a phenomenological approach. The basis for determining this approach refers to the paradigm put forward by Edmund Husserl, namely the use of awareness of reality and the expression of consciousness behind that reality. This study found the role of local wisdom "Pengataa" in minimizing the impact of disasters over a long period and organizing settlements free from the impacts of Nalodo.